Development of an Personalized Adaptive Learning Systemto improve students learning performances - et. al., Pratik Jadhav, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Computer-assisted education promises open access to top-class instruction and a reduction in the cost of learning. Also, the modern education system has achieved great success in knowledge education, but its role in quality education is unclear. In the traditional one-on-many instructional approach, learning models and continuing education programs are only based on a uniform approach. Due to the limitation of factors like a teaching process, human power, learner's abilities, and so on, instructors only provide all students with the same materials, and they tend to use an identical teaching approach and the same rate of progress. In this approach, it is difficult to consider the learning needs of individual students. This implies that students dependent on instructors teaching skills so they cannot make effective use of class time to learn. On the other hand, students with insufficient proficiency levels may not be able to understand the content of the course. Researchers are developing adaptive techniques that provide a better educational experience for students in some ways. Researchers offer accurate and perso-nalized content to students in an intelligent way, that may allow for adjustments in course content based on student's most recent performances. This technique allows the student to skip unnecessary learning activities by providing automated and personalized support for the student. These systems provide personalized course units that meet different student's educational needs.